English for academic purposes an advanced resource book - Hyland, Ken (Routledge applied linguistics, 2006)
Routledge Applied Linguistics is a series of comprehensive resource books, providing students and researchers with the support they need for advanced study in the core areas of English Language and Applied Linguistics.